PERLUASAN ORIENTASI PENDIDIKAN POLITIK MELALUI MKU - Lusila Andrirni Purwastuti Lusila Andrirni Purwastuti (Jurnal Cakrawala Pendidikan, 1998)
The political condition in Indonesia is poor at prescnt.This condition is caused by a lot of factors. The nlaill factor causing it is the existing poitical structure, which is clot functional. Another factor is the inappropriate practice of political education for society iin general and students inparticular. This present inappropriate political education iisfocussed on how to obtain power and how to guarantee nationalstability, so Ihat it does not reach the most fundamentaldimension of human life, namely, human rights. Therefore, it isabout time that the orientation of political education beextended.The political education should not be simply oriented ropolitical socialization of human rights. The reasons are that,firstly, political rights are just a small part of human rigl~ls,secondly, human rights are a dominant issue in the globali7ationera, and, thirdly, political education is essentially opening theconsciousness that the political field is not a means of actualizingpower values but rather a means of actualizing the noble valuesof humanism.One part of society to be the target of political educatio~~is college students, to whom the political education oriented tohuman rights can be performed through formal or nonformaleducation. In the college, political education is curricularlyintegrated in the general subject classes. In the course of theconversion of IKIP into a university, the MKU (short for MataKuliah Umum, meaning general subject classes) can be thestepping stones to initiate the implementation of politicalcducation oriented to human rights. There should be ways tointegrate the values of human rights into the general subjectclasses as a whole in order that these classes can equip studentsin becoming more mature and responsible in playing a part inthe political field so that it will finally help to bring the politicalcondition in Indonesia to becoming one more human.